SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS OF SYSTEMATIC ANALYSIS OF THE PEDAGOGICAL PROCESS - Raxmonov Vohidjon (TADQIQOTLAR, 2025)
ABSTRACT This  article  examines  the  scientific  and  methodological  foundations  of systematic analysis of the pedagogical process. It highlights the role, essence, structure, and components of a systematic approach in pedagogical analysis. The interrelation of systematic, activity-based, and learner-centered approaches and their importance in analyzing  pedagogical  systems  are  discussed.  The  article  also  outlines  the  factors enhancing the effectiveness of the pedagogical process through systematic analysis.